2019
DOI: 10.1177/1084822319863308
|View full text |Cite
|
Sign up to set email alerts
|

Health Promotion Practices in Nursing for Elderly Persons in Municipal Home Care: An Integrative Literature Review

Abstract: Elderly patients sometimes seek emergency services unnecessarily. Emergency clinics can be detrimental to the elderly. The purpose of this study was to find health promotion practices that enable a registered nurse in community health to reduce the need for home care clients to seek emergency care. The method of integrative literature review was used. Through health promotion work in the home, the registered nurses in community health (in conjunction with other professionals) can strengthen patients’ self-este… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
0
10
0
1
Order By: Relevance
“…For the individual patient, trauma may have a significant impact [ 46 ] because the return to their normal living environment may be challenging or impossible, during the process of safe discharge to a skilled nursing facility rather than home [ 47 ]. The increased demand in specialised nursing homes for geriatric patients with increasing incidence in medical comorbidities and chronic medical conditions is confronted by the limited capacity of nursing facilities [ 48 , 49 ] and will cause an economic challenge for the society.…”
Section: Discussionmentioning
confidence: 99%
“…For the individual patient, trauma may have a significant impact [ 46 ] because the return to their normal living environment may be challenging or impossible, during the process of safe discharge to a skilled nursing facility rather than home [ 47 ]. The increased demand in specialised nursing homes for geriatric patients with increasing incidence in medical comorbidities and chronic medical conditions is confronted by the limited capacity of nursing facilities [ 48 , 49 ] and will cause an economic challenge for the society.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this qualitative study reiterated that clinical classes, as a form of teaching, allow for an integration of theory and practice in learning [23], influencing the perception of students about health promotion and disease prevention in the elder. The connection between "school desk" knowledge and practice is vital to support the making of clinical decisions [24], and in this concrete case, for the learning of strategies that allow for the health promotion of the more vulnerable elder population. We corroborated the findings according to which elders with multiple morbidities need more complex health care, and health promotion is still not a priority for this group of people [25].…”
Section: Discussionmentioning
confidence: 99%
“…The outcome of such programs is early discharge from the hospital, the reduction of hospital workload, and the empowerment of care-seekers in self-care [ 53 ]. In a review study, Karlsson pointed out the impact of home visit programs on reducing unnecessary emergency visits by the elderly and the development of elderly self-care [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Karlsson’s study showed that the clients with chronic illnesses were satisfied with nursing counseling. The clients were less inclined to visit a doctor frequently, for they needed to spend more time and money [ 54 ].…”
Section: Discussionmentioning
confidence: 99%